Techno-economic analysis of biofuel production via bio-oil zeolite upgrading: an evaluation of two catalyst regeneration systems - Shemfe, Mobolaji B.; Gu, Sai; Fidalgo Fernandez, Beatriz (Elsevier, 2017)
Biofuels have been identified as a mid-term greenhouse gas (GHG) emissions abatement solution for decarbonising the transport sector. This study examines the techno-economic analysis of biofuel production via biomass fast pyrolysis and subsequent bio-oil upgrading via zeolite cracking. The aim of this study is to compare the techno-economic feasibility of two conceptual catalyst regeneration configurations for the zeolite cracking process: (i) a two-stage regenerator operating sequentially in partial and complete combustion modes (P-2RG) and (ii) a single stage regenerator operating in complete combustion mode coupled with a catalyst cooler (P-1RGC). The designs were implemented in Aspen Plus® based on a hypothetical 72 t/day pine wood fast pyrolysis and zeolite cracking plant and compared in terms of energy efficiency and profitability. The energy efficiencies of P-2RG and P-1RGC were estimated at 54% and 52%, respectively with corresponding minimum fuel selling prices (MFSPs) of £7.48/GGE and £7.20/GGE. Sensitivity analysis revealed that the MFSPs of both designs are mainly sensitive to variations in fuel yield, operating cost and income tax. Furthermore, uncertainty analysis indicated that the likely range of the MFSPs of P-1RGC (£5.81/GGE − £11.63/GGE) at 95% probability was more economically favourable compared with P-2RG, along with a penalty of 2% reduction in energy efficiency. The results provide evidence to support the economic viability of biofuel production via zeolite cracking of pyrolysis-derived bio-oil.
Keywords: Zeolite cracking; Bio-oil; Aspen plus; Fast pyrolysis; Uncertainty analysis; Techno-economic analysis